(untitled) (KONFERENSIYA, 2025)
In this article the linguistic characteristics and translation challenges of rendering English onomotopoeias into Uzbek ,focusing on their stylistic and functional roles within literary texts .The research is based on a table containing various onomatopoeic units natural sounds . Onomatopoeias , which strenghten imagery ,emotional tone ,and expressiveness in literary language ,require careful strategies to achieve proper equivalence in translation . The article compares translation approaches to sound –imitating words related to animals such as –cats ,dogs and birds as well as other sound sources . Aditionally , examples from literary works are used to highlight the importance of maintaining semantic , phonetic and stylistic consistency in translation